Gap between recommended and actual practice in pediatric obsessive–compulsive disorder. (March 2012) - Ale, Chelsea M; Storch, Eric A
SUMMARY Pediatric obsessive–compulsive disorder is a debilitating disorder that has a clear evidence base for what treatments 'work'' (i.e., cognitive-behavioral therapy and serotonin-reuptake inhibitor medications). Yet, the provision of such therapies does not follow practice parameters resulting in suboptimal treatment response and the potential for adverse health outcomes. This article will present widely used clinical practices for pediatric obsessive–compulsive disorder that are at odds with evidence-based practice guidelines. Potential areas for remediation in training and dissemination efforts will be highlighted.